2016
DOI: 10.1097/mib.0000000000000832
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Nonalcoholic Fatty Liver Disease by Serum Biomarkers in Patients with Inflammatory Bowel Disease

Abstract: NAFLD is a frequent comorbidity in patients with IBD. These patients can also develop advanced liver fibrosis. Disease activity, duration of IBD and prior surgery are predictors of NAFLD development. This should represent one more incentive to achieve and maintain early clinical remission. Further prospective studies are of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
120
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(130 citation statements)
references
References 47 publications
6
120
0
4
Order By: Relevance
“…Similar association have been made between psoriasis and NAFLD[28]. Duration of IBD was another independent predictor of development of NAFLD in the aforementioned Bessissow et al[22] study. Longer disease duration exposes patients to multiple risk factors for NAFLD, including chronic relapsing inflammation, alteration of gut microbiota and hepatotoxic drugs.…”
Section: Pathogenesissupporting
confidence: 75%
See 1 more Smart Citation
“…Similar association have been made between psoriasis and NAFLD[28]. Duration of IBD was another independent predictor of development of NAFLD in the aforementioned Bessissow et al[22] study. Longer disease duration exposes patients to multiple risk factors for NAFLD, including chronic relapsing inflammation, alteration of gut microbiota and hepatotoxic drugs.…”
Section: Pathogenesissupporting
confidence: 75%
“…A study from our group using the validated hepatic steatosis index (HSI) longitudinally followed 321 IBD patients over 7 years (217 CD, 104 UC)[22]. HSI, defined as: 8 × AST/ALT + BMI (+2, if female; +2, if diabetes), was applied to diagnose hepatic steatosis if the score is ≥ 36.…”
Section: Epidemiology: Prevelance Of Nafld In Ibdmentioning
confidence: 99%
“…A recent study reported an even higher incidence rate of NAFLD in IBD patients without underlying liver disease, using the validated Hepatic Steatosis Index . NAFLD was reported in one‐third of the patients, accounting for an incidence rate of 9.1/100 patient‐years (95% CI, 7.4‐10.9), which is higher than the general population (.029‐3.1/100 patient‐years).…”
Section: Other Hepatic Manifestations Than Psc Affecting Ibd Patientsmentioning
confidence: 99%
“…Duration of IBD is probably another independent predictor of NAFLD development . Disease exposes patients to multiple risk factors for NAFLD, including chronic relapsing inflammation, alteration of gut microbiota and hepatotoxic drugs.…”
Section: Other Hepatic Manifestations Than Psc Affecting Ibd Patientsmentioning
confidence: 99%
“…The rate of NAFLD likely depends on environmental and genetic risk factors of study population, as a recent prospective Swedish study detected lower rates of NAFLD than American studies [53]. Disease specific risk factors for NAFLD in patients with IBD include small bowel surgery, use of steroids, and disease duration and activity [52, 54]. As the prevalence of NAFLD and subsequently nonalcoholic steatohepatitis induced cirrhosis, increases in patients with IBD, liver failure, and transplantation will complicate management of patients with IBD.…”
Section: Comorbiditiesmentioning
confidence: 99%